Aging effect and antibody immobilization on -COOH exposed surfaces designed for dengue virus detection - Hosseini, S.; Ibrahim, F.; Rothan, H.A.; Yusof, R.; van der Marel, C.; Djordjevic, I.; Koole, L.H. (Elsevier, 2015)
Polymethylmethacrylate-co-methacrylic acid, poly(MMA-co-MAA) coatings were produced with different initial molar ratios of monomers (MMA and MAA) in free-radical polymerization reaction. Polymeric platforms were specifically designed with controlled concentration of surface-exposed carboxyl (-COOH) groups that can be used as a desirable functionality for protein immobilization. Spin-coated chips were used for antibody (Ab) immobilization in order to investigate the influence of -COOH surface concentration on dengue virus detection efficiency in enzyme-linked immunosorbent assay (ELISA) experiment. Successful immobilization of Ab was achieved by two different techniques: (1) physical adsorption; and (2) covalent immobilization by carbodiimide coupling between the surface -COOH groups and amine functionalities of dengue Ab molecules. Produced polymer coatings were characterized with surface spectroscopy techniques (Raman and X-ray photoelectron spectroscopy, XPS) and water-in-air contact angle (WCA) measurements. In particular, this research concentrated on the aging effect on the availability and activity of surface -COOH groups. For that reason, WCA and Ab immobilization (ELISA) experiments were repeated on coated biochips after 3,6 and 9 months of storage. Results in this paper describe the robust and sustainable functionalized polymeric platform that can be used effectively for protein activation and development of novel biosensors. (C) 2015 Elsevier B.V. All rights reserved.